Sensitivity Analysis of Gas Retrieval from FS MAX-DOAS Measurements - Jiangman Xu; Ang Li; Zhaokun Hu; Hongmei Ren (Remote Sensing)
Multi-axis differential absorption spectroscopy (MAX-DOAS) has become an important tool for detecting trace gases in optical remote sensing. At present, the temporal resolution of the system using the traditional motor-rotated elevation telescope is extremely low. We focus on studying the atmospheric radiation transmission of fast synchronous MAX-DOAS (FS MAX-DOAS), which has greatly improved the temporal resolution on the ground and on mobile platforms and the influence of related parameters on the atmospheric mass factor (AMF), which is used to guide the design and experiments of the new system. The optimal elevation angle combination, the spectral resolution, and the specific effects of relevant parameters on the AMF during profile inversion by the new system were analyzed, and the feasibility of the new system for mobile MAX-DOAS was evaluated. The inversion results of the measured spectra collected by the system show that FS MAX-DOAS can meet the requirements of both ground and mobile platform observation scenarios. The results of our sensitivity study are of great significance for guiding experiments.